The myth of consumption and the representation of solitude in Indonesian urban popular music - Indrasmara, Piwi Ray; Husaini, Amri; Fajaruddin, Syarief (LINGUISTICA, 2025)
This study investigates how solitude is signified in the lyrics of Orgasme dengan Sepeda by TheKick through Roland Barthes’ semiotic framework. Specifically, it maps signs that represent health, hedonism, and social recognition; explains the syntagmatic–paradigmatic relations that generate irony; and interprets the cultural implications of these representations. The method applies Barthes’ three layers of meaning—denotation, connotation, and myth—to lyric data. The findings indicate that solitude does not appear literally but emerges as a paradox between a healthy image and consumptive practice. The sign “bicycle” shifts from a symbol of fitness to a representation of social status and self-performance in digital media. Interrelations among signs produce the irony that efforts to appear healthy and trendi in fact intensify existential loneliness. The study concludes that solitude in Indonesian popular culture arises from consumerist orientations and the pursuit of social validation, rather than from physical separation. These results extend cultural semiotics by showing that the myth of consumption also operates through performative lifestyle activities and musical expression.